The study of structural development of expanded austenite on duplex stainless steel by low temperature thermochemical nitriding process / Lailatul Harina Paijan - Paijan, Lailatul Harina (2014)
This research project describes the study of gaseous thermochemical treatment of nitriding duplex stainless steel (DSS) by using a tube furnace. DSS is widely used in various industries such as petrochemical, chemical processing plant and others. However, this material experiences wear and hardness failure during service.Therefore, new development of low temperature nitriding has been introduced to improve the surface properties of this material. The improvement of wear properties and hardness relies on the development of a hard layer on the surface. The nitriding was performed in a temperature range between 400°C, 450°C and 500°C for 6 and 14 hours. The gas composition used for this study was 50% NH3+ 50% N2 and 250/0 NH3 + 75% N2• The structural development was characterised using microhardness, X-ray diffraction (XRD), optical microscope, scanning electron microscopy (SEM) and wear resistance test. Based on this study, at a constant temperature of450°C with 50%'NH3 had produced highest thickness for expanded austenite with 13.96 urn for 6 hours treatment and increased to 76.17 urn for 14 hours treatment. This also led to a significant increase on top surface hardness about 666.3 HV and 962.59 HV for 6 and 14 hours treatment, respectively. For XRD analysis, it clearly shows that Bragg reflections (peaks) for nitrided samples are slightly shifted to lower 29 angles compared to untreated sample due to formation of expanded austenite. However, increased treatment temperature to 500°C with 25% and 50% ammonia can lead to the formation of chromium nitride precipitates in the nitrogen enriched layer, and thus deteriorate the corrosion resistance of material. It is hope that the study can contribute to the improvement of surface engineering technology of this material for wide range application purposes.